Stephen Neill, Missions, and the Ecumenical Movement - Daughrity, Dyron B. (International review of mission, 2005)
The present article summarizes Bishop Stephen Neill's (1900–1984) ecumenical activities, contextualizing them within his long, illustrious career. While the purpose of this article is not to address the sufficiency or deficiency of the ecumenical movement's focus on missions, it does contribute to that discussion. Neill was one who understood the interdependent relationship of ecumenism and missions. His life and work was a manifestation of that correlative relationship. Stephen Neill emphasized that missions is not peripheral to ecumenism; rather, ecumenism is rooted in missions.